Assessment of the accuracies of estimated breeding values and genomic enhanced breeding values in selection of Bonsmara cattle - Van Marle-Koster, Este (University of Pretoria, 2021)
Dissertation (MSc (Agric): Animal Breeding and Genetics)--University of Pretoria, 2020.